Asuhan Keperawatan pasien dengan Penyakit Paru Obstruksi Kronis (PPOK) di Ruang Inap Paru RSUD Prof. H. Muhammad Yamin, SH - Chitra Ananda; Kheniva Dwi Anggita; Mike Asmaria; Aulia Asman (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic, progressive, and frequently occurring health condition characterized by airflow obstruction caused by chronic bronchitis or. According to the World Health Organization, COPD ranks fourth as the leading cause of death globally, with approximately 3.5 million deaths caused by this disease. The purpose of writing this scientific paper is to provide nursing care to patients with COPD. The research method used in this Scientific Paper is a case study method that includes death assessment, death diagnosis, death intervention, death implementation, death evaluation and death documentation. The results of the study found 4 poisoning problems that appeared in the patient, namely Airway Clearance, Ineffective Breathing Pattern, Activity Intolerance, and Sleep Pattern Disorders. The results of the case study obtained Interventions that were arranged included effective coughing exercises, airway management, activity therapy, and sleep support. Based on the evaluation of accommodation for 4 days, it showed that the patient had improved as indicated by reduced shortness of breath, was able to cough effectively, activity intolerance had improved and sleep patterns had improved. Suggestions from this study can improve professional skills in medical-surgical care, enable patients and their families to receive care and adopt a healthy lifestyle, enable hospitals to serve as a reference in providing surgical care, and enable educational institutions to utilize the study as learning material for students regarding COPD.